Navigating the tensions: women’s rights, religion and freedom of religion or belief - Ghanea, Nazila (Religion and human rights, 2021)
Abstract Despite the normative integration between freedom of religion or belief (FORB) and women’s equality, these synergies are difficult to discern and there is a common misperception that women’s rights to equality and FORB are clashing rights. This is compounded by the extensive religiously phrased reservations by states upon ratification of international treaties that amplify this misperception that FORB serves to restrict women’s rights to equality. The advocacy groups supporting these rights, and also their normative sources in international human rights law instruments, are largely distinct. However, general non-discrimination provisions do address both, and General Comment no. 28 captures both rights holistically. The correctives to these misperceptions lie in reflecting upon the universality, indivisibility, interdependence, and interrelatedness of all human rights norms. They also lie in the realization that FORB is a right like any other. FORB is neither a right of “religion” as such nor an instrument for support of religiously phrased reservations and limitations on women’s rights to equality. This is particularly the case with harmful practices, as elaborated in the joint general recommendation/General Comment no. 31 of the Committee on the Elimination of All Forms of Discrimination against Women and no. 18 of the Committee on the Rights of the Child however, the core principles also extend to other infringements of women’s rights to equality. It is essential to (re)vitalize the synergies between FORB and women’s equality in order to advance each of these rights, to be able to address overlapping rights concerns, and to adequately acknowledge intersectional claims. Furthermore, the relevant advocacy groups and human rights mechanisms need to give further attention to this as a priority matter.